Weight management program focusing on body composition and physical activity at a primary care clinic - Kamaruzaman, Nor Azam; Abd Rahman, Mohd Aizuddin; Pasi, Hafizah (2023)
Overweight and obesity are increasingly prevalent with a ratio of 1 in 2 among adult Malaysian. 65 percent of staff in a primary care clinic was found to be either obese or overweight. A program (Fat 2 Fit) with the aim to empower clinic members to achieve reduction in body fat (BF%) and weight (BMI), improve fitness and build teamwork was initiated in August 2022.